The Cross-Protective Immunity Landscape Among Different SARS-CoV-2 Variant RBDs - Sun, Wenqiang; He, Lihong; Lou, Huicong; Fan, Wenhui; Yang, Limin; Cheng, Gong; Liu, Wenjun; Sun, Lei (Frontiers in Immunology, 2022)
Despite the fact that SARS-CoV-2 vaccines have been available in most parts of the world, the epidemic status remains grim with new variants emerging and escaping the immune protection of existing vaccines. Therefore, the development of more effective antigens and evaluation of their cross-protective immunity against different SARS-CoV-2 variants are particularly urgent. In this study, we expressed the wild type (WT), Alpha, Beta, Delta, and Lambda RBD proteins to immunize mice and evaluated their cross-neutralizing activity against different pseudoviruses (WT, Alpha, Beta, Delta, Lambda, and Omicron). All monovalent and pentavalent RBD antigens induced high titers of IgG antibodies against different variant RBD antigens. In contrast, WT RBD antigen-induced antibodies showed a lower neutralizing activity against Beta, Delta, Lambda, and Omicron pseudoviruses compared to neutralization against itself. Interestingly, Beta RBD antigen and multivalent antigen induced broader cross-neutralization antibodies than other variant RBD antigens. These data provide a reference for vaccine strain selection and universal COVID-19 vaccine design to fight the constant emergence of new SARS-CoV-2 variants.